2015
DOI: 10.7863/ultra.15.14.10060
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Sheath Diameter Increase on Ascent to High Altitude

Abstract: The mean optic nerve sheath diameter increased on ascent to high altitude compared to baseline values, but not to a statistically significant degree. The magnitude of the observed Δ optic nerve sheath diameter was positively associated with acute mountain sickness diagnosis. No such significant association was found between acute mountain sickness and diameter elevation above standard cutoff values, limiting the utility of sonography as a diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Ultrasonography has been attempted as a clinical prognosticator at high altitudes [23] but with limited diagnostic success as a point estimate of AMS [24]. Similar to other high-altitude ultrasound studies [13], our results indicated that a single measurement of intravascular volume has limited applicability and is not a useful clinical adjunct to the evaluation and performance determinant of high-altitude mountaineers.…”
Section: Discussionsupporting
confidence: 49%
“…Ultrasonography has been attempted as a clinical prognosticator at high altitudes [23] but with limited diagnostic success as a point estimate of AMS [24]. Similar to other high-altitude ultrasound studies [13], our results indicated that a single measurement of intravascular volume has limited applicability and is not a useful clinical adjunct to the evaluation and performance determinant of high-altitude mountaineers.…”
Section: Discussionsupporting
confidence: 49%
“…Portable ultrasound devices allow non-invasive evaluation of many neuroimaging parameters of interest during high altitude research. Ultrasonography of the optic nerve sheath diameter (ONSD) has been shown to be a reliable tool for diagnosis of increased intracranial pressure (ICP) in a hospital setting in neurocritical patients1213, and ONSD changes have previously been associated with AMS and HACE141516. Despite the assumption that ONSD reflects changes in brain volume, the pathophysiological and clinical significance of increased ONSD in subjects exposed to hypobaric hypoxia is still unclear.…”
mentioning
confidence: 99%
“…Although we agree that a change in the baseline optic nerve sheath diameter on ascent to high altitude is interesting for pathophysiologic research, we think that this sonographic modality is not practical for most clinical scenarios in the wilderness at high altitude or as an adjunct diagnostic tool, as supported by a recently published systematic review by your research group. 6 We tempered our conclusions by noting that our observed association of a larger Δ optic nerve sheath diameter and acute mountain sickness is an interesting one but not sufficient to recom-…”
Section: Replymentioning
confidence: 72%